THE LEGAL SITUATION OF PEOPLE WITH DISABILITIES IN LATVIA - Kulačkovska, Judīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Each year the number of people with disabilities in Latvia increases. More and more children are born with congenital problems. Many opportunities are not used to integrate disabled people in the society. The study aims to evaluate the legal situation in Latvia of both children and adults with disabilities. People with functional disorders are an integral part of society and the legislative framework should prevent their discrimination. While carrying out the analysis of legal framework defining documents, as well as the reflection of personal experience, it was found that the actual situation in the country does not entirely meet with the legal framework. People with special needs in both Latvian statutes and everyday life are still denoted with a term ’invalid’. In assessing the dynamics of the number of disabled children, it was found that the number of such children is increasing.